Menyoal Kebebasan Beragama dan Penodaan Agama Di Indonesia - Yayan Sopyan (Jurnal Cita Hukum, 2015)
Abstract: Questioning the Religious Freedom and blasphemy in Indonesia. The presence of the Constitutional Court in the reform era is the strengthening of the foundations of constitutionalism in the Constitution of the Republic of Indonesia Year 1945. The Court in this case a role to enforce and the protector of the citizen's constitutional rights and the protector of the human rights. Including in this case, the right to religion and religious practices and teachings of their respective religions, in accordance with the constitutional mandate. However, on the other hand there is the discourse of freedom of expression and freedom of speech includes freedom to broadcast religious beliefs and understanding of the "deviant" and against the "mainstream" religious beliefs and understanding in general, as in the case of Ahmadiyah. The Court in this case is required to provide the best attitude when faced judicial review in this case still required in addition to guarding the constitution in order to run properly.   Abstrak: Menyoal Kebebasan Beragama dan Penodaan Agama di Indonesia. Kehadiran lembaga Mahkamah Konstitusi di era reformasi merupakan upaya penguatan terhadap dasar-dasar konstitusionalisme pada Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. MK dalam hal ini berperan menegakkan dan melindungi hak-hak konstitusional warga negara (the protector of the citizen’s constitutional rights) dan pelindung HAM (the protector of the human rights). Termasuk dalam hal ini, hak untuk memeluk agama dan menjalankan ibadah serta ajaran agamanya masing-masing, sesuai dengan amanat konstitusi. Namun, disisi lain ada wacana kebebasan berekspresi dan kebebasan berpendapat termasuk didalamnya kebebasan untuk menyiarkan keyakinan dan pemahaman keagamaan yang “menyimpang” dan bertentangan dengan “mainstream” keyakinan dan pemahaman keagamaan pada umumnya, seperti dalam kasus Ahmadiyah. MK dalam hal ini dituntut untuk mampu memberikan sikap terbaik saat dihadapkan judicial review dalam kasus ini selain tetap dituntut untuk mengawal konstitusi agar dapat berjalan sebagaimana mestinya. DOI: 10.15408/jch.v2i2.2314